Preparation of sesquiterpene lactone derivatives: Cytotoxic activity and selectivity of action - Beer, Maria Florencia (2019)
Cancer is one of the most important causes of death worldwide. Solid tumors represent the great majority of cancers (>90%) and the chemotherapeutic agents used for their treatment are still characterized by variable efficacy and toxicity. Sesquiterpene lactones are a group of naturally occurring compounds that have displayed a diverse range of biological activities including cytotoxic activity. A series of oxygenated and oxy-nitrogenated derivatives (4–15) from the sesquiterpene lactones cumanin (1), helenalin (2), and hymenin (3) were synthesized. The silylated derivatives of helenalin, compounds 13 and 14, were found to be the most active against tumor cell lines, with GI50 values ranging from 0.15 to 0.59 µM. The ditriazolyl cumanin derivative (11) proved to be more active and selective than cumanin in the tested breast, cervix, lung, and colon tumor cell lines. This compound was the least toxic against splenocytes (CC50 = 524.1 µM) and exhibited the greatest selectivity on tumor cell lines. This compound showed a GI50 of 2.3 µM and a SI of 227.9 on WiDr human colon tumor cell lines. Thus, compound 11 can be considered for further studies and is a candidate for the development of new antitumor agents.